Performance Improvement of Microcrystalline p-SiC/i-Si/n-Si Thin Film Solar Cells by Using Laser-Assisted Plasma Enhanced Chemical Vapor Deposition - Hsin-Ying Lee; Ting-Chun Wang; Chun-Yen Tseng (International Journal of Photoenergy)
The microcrystalline p-SiC/i-Si/n-Si thin film solar cells treated with hydrogen plasma were fabricated at low temperature using a CO2 laser-assisted plasma enhanced chemical vapor deposition (LAPECVD) system. According to the micro-Raman results, the i-Si films shifted from 482 cm−1 to 512 cm−1 as the assisting laser power increased from 0 W to 80 W, which indicated a gradual transformation from amorphous to crystalline Si. From X-ray diffraction (XRD) results, the microcrystalline i-Si films with (111), (220), and (311) diffraction were obtained. Compared with the Si-based thin film solar cells deposited without laser assistance, the short-circuit current density and the power conversion efficiency of the solar cells with assisting laser power of 80 W were improved from 14.38 mA/cm2 to 18.16 mA/cm2 and from 6.89% to 8.58%, respectively.